Interactions among the mycobiome, bacteriome, inflammation, and diet in people living with HIV. (31st December 2022) - Gosalbes, María José; Jimenéz-Hernandéz, Nuria; Moreno, Elena; Artacho, Alejandro; Pons, Xavier; Ruíz-Pérez, Sonia; Navia, Beatriz; Estrada, Vicente; Manzano, Mónica; Talavera-Rodriguez, Alba; Madrid, Nadia; Vallejo, Alejandro; et al.
ABSTRACT: While the intestinal microbiome seems a major driver of persistent immune defects in people with HIV (PWH), little is known about its fungal component, the mycobiome. We assessed the inter-kingdom mycobiome–bacteriome interactions, the impact of diet, and the association with the innate and adaptive immunity in PWH on antiretroviral therapy. We included 24 PWH individuals and 12 healthy controls. We sequenced the Internal Transcribed Spacer 2 amplicons, determined amplicon sequence variants, measured biomarkers of the innate and adaptive immunity in blood and relations with diet. Compared to healthy controls, PWH subjects exhibited a distinct and richer mycobiome and an enrichment for Debaryomyces hansenii, Candida albicans, and Candida parapsilosis . In PWH, Candida and Pichia species were strongly correlated with several bacterial genera, including Faecalibacterium genus. Regarding the links between the mycobiome and systemic immunology, we found a positive correlation between Candida species and the levels of proinflammatory cytokines (sTNF-R2 and IL-17), interleukin 22 (a cytokine implicated in the regulation of mucosal immunity), and CD8+ T cell counts. This suggests an important role of the yeasts in systemic innate and adaptive immune responses. Finally, we identified inter-kingdom interactions implicated in fiber degradation, short-chain fatty acid production, and lipid metabolism, and an effect of vegetable and fiber intake on the mycobiome. Therefore, despite the great differences in abundance and diversity between the bacterial and fungal communities of the gut, we defined the changes associated with HIV, determined several different inter-kingdom associations, and found links between the mycobiome, nutrient metabolism, and systemic immunity.